Psychoeducation for the Teaching of Psychological Techniques based on the Levenstein Test adapted to Spanish. - Sánchez Jiménez, Kevin Andrés; Quevedo Mora, Victor Ernesto; Ulloa Castro, Jefferson Enrique; Valencia Valle, Aldo Armando (Conexiones UG, 2025)
This study examines the perception of workload from the perspective of administrative employees, employing the Perceived Stress Questionnaire (PSQ) by Levenstein, linguistically adapted to Ecuadorian Spanish. The instrument, consisting of 30 items applied at two time points, evaluates stress levels across diverse populations. Results indicate high levels of perceived workload over both general (1–2 years) and specific (last month) periods, revealing a strong link between excessive work demands and adverse effects on employees’ physical and mental health, including burnout syndrome. The research emphasizes the importance of strategies to mitigate stress, such as effective time management, coping skills (mindfulness and cognitive reappraisal), relaxation techniques (diaphragmatic breathing and progressive muscle relaxation), stress psychoeducation, and strengthening social support networks. These interventions not only alleviate perceived workload but also foster overall well being and enhance organizational productivity.